(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This paper conducts a comprehensive exploration of decision-making concepts in economics and finance, tracing the evolution from the concept of Rationality and Rational Choice Theory (RCT). The study extends beyond traditional frameworks to cover the downfall of rationality in economics and finance theories giving rise to bounded rationality and satisficing theory. It also covers the Dual Systems in Human Decision-Making, substantiating this basis with evidence from the fields of psychology and neuroscience. Further, going beyond rationality, some key theories/concepts are explored such as prospect theory, heuristics, biases, and social-cultural norms, etc., that explain the cognitive processes behind decision-making and bring forth the external influences that influence decisions in economics and finance. Through an extensive study of available literature, uniting diverse perspectives and ongoing insights that stretch beyond conventional economic and financial paradigms, this paper aims to provide an inclusive understanding of the theoretical and conceptual development of decision-making over the years.